BEYOND POLLEN AND SPORES: THE CONTRIBUTION OF NON POLLEN PALYNOMORPHS IN PALAEOENVIRONMENTAL STUDIES - Κούλη Κ.; Δερμιτζάκης Μ. Δ. (Bulletin of the Geological Society of Greece, 2006)
Non-pollen palynomorphs (ΝΡΡ) are organic-walled microfossils that are frequently discovered in palynological preparations during pollen analysis. Like pollen and spores they are resistant to corrosion and they survive the chemical preparation with heavy acids of pollen samples. NPP include a big variety of microfossils like fungal spores, algal spores and coenobia, animal remains and plant tissues. They provide an alternative source of paleoecological information especially for the Quaternary. A combined approach of pollen and NNP allows the better understanding of paleoecological changes. The study of occurrences of NNP from a series of Holocene deposits in Greece (Lake Kastoria, Skyros Island, Marathon coastal plain) was proved of great importance in the interpretation of paleoenvironmental conditions and the tracing of human activities in the past.